Analyze the Factors Influencing Purchase Intention at PT MPI Cikarang Indonesia - Kuswibowo, Christian; Afifah, R. Dinda Azhar (inovator, 2024)
This study aims to identify the factors that influence the purchase decision of car components at PT Multi Pratama Interbuana Cikarang, West Java. The factors used in this study were built from the dimensions of the marketing mix, namely Product, Price, Place and Promotion. This research is a quantitative study with factor analysis and descriptive analysis through the help of the PASW Statistics 18 statistical program. This research method used the entire population because only 42 respondents at PT Multi Pratama Interbuana Cikarang, Bekasi, West Java who met the requirements of the population and sample. Sources of data used in this study is primary data. As the results of the research, it was found that the factors those shape purchase decisions at PT Multi Pratama Interbuana Cikarang, West Java are the Price Conformity factor, the Easy Access factor, and the Prod- uct Quality factor.